Navigating advanced polycystic kidney disease: a case study of bilateral nephrectomy and life-saving transplant - Suooda, Fathimath; Maleesha, Fathimath; Ali, Fathmath Zuha; Ivanovna, Yulia Karpovich (International Journal of Research in Medical Sciences, 2025)
This case report discusses a 60-year-old female with polycystic kidney disease (PKD) who developed end-stage renal disease (ESRD). Diagnosed with polycystic kidney and liver disease in 2004, her condition worsened over the years, ultimately requiring hemodialysis and, later, kidney transplantation. Pre-transplant preparations included bilateral nephrectomy due to extensive cystic involvement of both kidneys. Post-transplant follow-up showed marked improvement in kidney function, with careful management using immunosuppressive, antifungal, and antihypertensive medications to prevent rejection and infection. This case underscores the critical role of multidisciplinary care in PKD patients undergoing transplantation for ESRD.